Residues from Medicinal and Aromatic Plants after Distillation Can Be Used in Replace Some Peat in the Growing Media for Viola × wittrockiana Production - Chrysargyris, Antonios; Tzortzakis, Nikos G. (My University, 2024)
Plant residues derived from the agro-industrial sector and their disposal are still unsolved issues despite the various research and applications. The current study assessed the possible peat substitution in growing media with solid residues derived from the distillation of Origanum dubium Boiss (OD) and Sideritis cypria Post (SC) after essential oils production. Residues of OD and SC (0–5–10–20% v/v) and their mixture (OD + SC) were examined to partially substitute peat for the production of pansy (Viola × wittrockiana) plants. The presence of OD, SC, and OD + SC residues increased the pH, the electrical conductivity, the organic matter content, and the levels of minerals in the growing media mixtures compared to sole peat while decreasing the total porosity (up to 36.8%) and the available free air (up to 58.3%). The OD residues’ presence in the peat-based media revealed more detrimental effects than the SC, while the OD + SC mixture received intermediate effects. Low residue ratios (≤5% OD, ≤10% SC, ≤10% OD + SC) sustain plant growth and photosynthetic activity of plants, while higher ratios decrease plant growth, chlorophyll content and mineral accumulation due to inappropriate growing media properties, causing plant oxidative stress. This was verified using the increase in malondialdehyde (up to 4.5 times) and hydrogen peroxide (up to 2.1 times) content in plants and the activation of several non-enzymatic antioxidant processes, including total phenols, flavonoids, and antioxidant capacity of the plants. Therefore, OD, SC, and OD + SC at 5%, 10%, and 10%, respectively, can partially substitute peat, as they result in appropriate plant growth and development. However, the growing media’s properties must be improved to ensure adequate yields as well.
Keywords: Antioxidants; Hydro-steam distillation; Lipid peroxidation; Minerals; Pansy